Phosphoric acid doped composite proton exchange membrane for hydrogen production in mediumtemperature copper chloride electrolysis - Kamaroddin, Mohd Fadhzir Ahmad; Sabli, Nordin; Nia, Pooria Moozarm; Tuan Abdullah, Tuan Amran; Abdullah, Luqman Chuah; Izhar, Shamsul; Ripin, Adnan; Ahmad, Arshad (Elsevier, 2020)
A copper chloride (CuCl) electrolyzer that constitutes of composite proton exchange membrane (PEM) that functions at medium-temperature (>100 °C) is beneficial for rapid electrochemical kinetics, and better in handling fuel pollutants. A synthesized polybenzimidazole (PBI) composite membrane from the addition of ZrO2 followed with phosphoric acid (PA) is suggested to overcome the main issues in CuCl electrolysis, including the copper diffusion and proton conductivity. PBI/ZrP properties improved significantly with enhanced proton conductivity (3 fold of pristine PBI, 50% of Nafion 117), superior thermal stability (>600 °C), good mechanical strength (85.17 MPa), reasonable Cu permeability (7.9 × 10−7) and high ionic exchange capacity (3.2 × 10−3 mol g−1). Hydrogen produced at 0.5 A cm−2 (115 °C) for PBI/ZrP and Nafion 117 was 3.27 cm3 min−1 and 1.85 cm3 min−1, respectively. The CuCl electrolyzer efficiency was ranging from 91 to 97%, thus proven that the hybrid PBI/ZrP membrane can be a promising and cheaper alternative to Nafion membrane.